2015
DOI: 10.1093/ntr/ntv149
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Dependence in Adolescence and Physical Health Symptoms in Early Adulthood

Abstract: Introduction: To examine the prospective associations of Diagnostic and Statistical Manual of Mental Disorders nicotine dependence (ND) and other individual and parental factors in adolescence on self-reported health symptoms in early adulthood. Methods: Multiethnic prospective longitudinal cohort of adolescents from grades 6-10 and a parent (N = 908) from the Chicago Public Schools. Adolescents were interviewed five times at 6-month intervals (Waves 1-5) and once 4.5 years later (Wave 6). Parents were intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…This rate aligns with prior work and is concerning as even intermittent, nondaily use can lead to nicotine dependence, 31,32 which is a strong predictor of physical health symptoms (eg, chest pain) in young adulthood. 33 This study highlights the critical need for adolescent smoking initiation and reduction efforts nationwide.…”
Section: Discussionmentioning
confidence: 90%
“…This rate aligns with prior work and is concerning as even intermittent, nondaily use can lead to nicotine dependence, 31,32 which is a strong predictor of physical health symptoms (eg, chest pain) in young adulthood. 33 This study highlights the critical need for adolescent smoking initiation and reduction efforts nationwide.…”
Section: Discussionmentioning
confidence: 90%
“…Epidemiological and clinical data have shown that exposure to tobacco or nicotine can lead to subsequent abuse of nicotine and other recreational drugs in adolescents, and this phenomenon is described as the gateway hypothesis ( 45 ). Parents can affect the health of their children through genetic factors, physical and mental health, health behaviors and socioeconomic status ( 11 ).…”
Section: Methodsmentioning
confidence: 99%
“…The urge to smoke occurs early on after initiation, which drives the increase in frequency of use, exacerbating into nicotine dependence and a more rapid progression to addiction and a neurophysiologic dependence on nicotine ( 9 ). The risk of nicotine dependence in adolescents is associated with intensity of recent cigarette consumption, a slower nicotine metabolism and depression ( 11 ). The CDC warns that if cigarette smoking continues at the current rate among youth, 5.6 million of Americans younger than 18 will die early from a smoking-related illness ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nicotine dependence (ND) is characterized by tolerance, craving, withdrawal symptoms in case of abstinence, loss of control over the number of cigarettes and the time spent smoking, unsuccessful attempts to quit, neglect of important activities, and smoking despite physical or psychological problems (Griesler et al 2016). Withdrawal symptoms due to nicotine include but are not limited to depressed mood, irritability, nervousness, anger, anxiety, trouble focusing, and impatience (Griesler et al 2016). The unpublished results of a recent national study conducted among adolescents revealed that the prevalence of moderate to high cigarette dependence was 21.8%.…”
Section: Introductionmentioning
confidence: 99%